AB0722 Survival, Causes of Death and Prognosis Factors in Systemic Sclerosis in Argentina. (9th June 2015) - Sansinanea, P.; Marcos, J.; Testi, A.; Pera, M.; Pena, C.; Salas, A.P.; García, M.A.
Abstract : Background: Systemic Sclerosis (SSc) is a progressive and disabling disease. The outcome of the disease varies from a relatively benign condition to a progressive disease with high mortality. Identifying the factors that determine survival in patients with SSc would contribute to establish prognosis and develop diagnostic and guided treatment strategies. Objectives: To analyze survival, cause of death and prognostic factors in a SSc cohort of patients in a tertiary referral hospital of Argentina. Methods: In a retrospective observational cohort study, 100 patients were registered during 1983-2013. Inclusion criteria: patients with diagnosis of SSc according 1980 ACR criteria and ≥18 years-old. Exclusion criteria: Early SSc, Convective tissue diseases that may overlap with SSc, sclerodermiform syndromes, lost of follow up. Patients were classified according ACR criteria and were divided according extension of cutaneous involvement in limited and diffuse form. Demographics, organ involvement (cutaneous, pulmonary, cardiac, digestive and renal) and laboratory (general parameters, antinuclear antibodies; anti-SCL-70 and anti-centromere antibodies) variables were assessed. Accumulated survivals at 5, 10, 15 and 20 years were estimated by Kaplan-Meier method. Cox method was performed to identify prognostic factors. Results: 83 women and 17 men were included in the study. The female/man ratio was 4-5:1. The age of onset of the disease was 43.5±16 years-old and the age at diagnosis was 47.61±14.7. The clinical forms were distributed in: 63% limited and 37% diffuse forms. Six-teen deaths were registered. In 9 patients, causes of death were strictly related with SSc (56%), 5 (31.2%) patients died due to pulmonary causes (ILD/PAH), 3 (18.7%) due to cardiac causes (arrhythmias and primary cardiomyopathies) and 1 due to gastrointestinal bleeding (gastric antral vascular ectasia). Deaths no related to SSc were associated with infections, cancer and primary biliary cirrhosis. 10 patients who died had diffuse SSc and 6 limited form. Survival curves were compared and lower survival was found in diffuse form with statistically significant difference (p=0.04). Global Survival at 5, 10, 15 and 20 years were of 89%, 83%, 75% and 69% respectively. When analyzing clinical subtypes, survival estimation of the limited form at 5, 10, 15 and 20 years was 92%, 90%, 84% and 82% respectively, while in the diffuse form was 84%, 71%, 65% and 54%. In multivariate analysis, independent poor prognostic factors were diffuse cutaneous disease (p=0.03; HR 3.38; IC95% 1.10-10.41) and lung involvement (p 0.05; HR 3.25; IC95% 0.98-10.79). Conclusions: In our cohort of SSc patients the survival at 5, 10, 15 and 20 years were of 89%, 83%, 75% and 69% respectively. The main causes of death were lung and cardiovascular compromise. The independent factors that showed significant consequences on the survival of SSc patients were the diffuse form and the lung involvement. No differences in survival based on anti-nuclear antibodies, anti-centromere and anti-scl70 were found. Disclosure of Interest: None declared